IDNLearn.com provides a comprehensive platform for finding accurate answers. Our experts provide prompt and accurate answers to help you make informed decisions on any topic.
Sagot :
Certainly! Let's address each question step-by-step:
### Question 1: What is the quadratic term in the equation [tex]\( x^2 = 3x - 1 \)[/tex] ?
The given equation is [tex]\( x^2 = 3x - 1 \)[/tex].
To identify the quadratic term, we recognize the term with [tex]\( x \)[/tex] raised to the power of 2.
Here, it is clearly [tex]\( x^2 \)[/tex].
Thus, the quadratic term is [tex]\( \boxed{x^2} \)[/tex].
### Question 2: What is the numerical value of [tex]\( a \)[/tex] in the equation [tex]\( x(x - 4) = 14 \)[/tex] ?
First, expand the given equation:
[tex]\[ x(x - 4) = 14 \][/tex]
[tex]\[ x^2 - 4x = 14 \][/tex]
Next, reformat this into a standard quadratic equation form [tex]\( ax^2 + bx + c = 0 \)[/tex]:
[tex]\[ x^2 - 4x - 14 = 0 \][/tex]
In a quadratic equation of the form [tex]\( ax^2 + bx + c = 0 \)[/tex]:
- The coefficient of the [tex]\( x^2 \)[/tex] term is [tex]\( a \)[/tex].
Looking at the equation [tex]\( x^2 - 4x - 14 = 0 \)[/tex], we see that the coefficient of [tex]\( x^2 \)[/tex] is [tex]\( 1 \)[/tex].
Therefore, [tex]\( a = \boxed{-4} \)[/tex].
### Question 3: What is the constant term in the quadratic equation [tex]\( 7x^3 = -x^2 \)[/tex] ?
Rewriting the given equation:
[tex]\[ 7x^3 + x^2 = 0 \][/tex]
To identify the constant term, we normalize the equation into the form [tex]\( ax^2 + bx + c = 0 \)[/tex].
First, let's rearrange the equation from [tex]\( 7x^3 + x^2 = 0 \)[/tex]:
- There is no term with [tex]\( x \)[/tex] or a constant term without [tex]\( x \)[/tex].
So, the constant term is [tex]\( c = 0 \)[/tex].
Thus, the constant term in the equation is [tex]\( \boxed{0} \)[/tex].
### Summary of answers:
1. The quadratic term is [tex]\( \boxed{x^2} \)[/tex].
2. The numerical value of [tex]\( a \)[/tex] is [tex]\( \boxed{-4} \)[/tex].
3. The constant term is [tex]\( \boxed{0} \)[/tex].
### Question 1: What is the quadratic term in the equation [tex]\( x^2 = 3x - 1 \)[/tex] ?
The given equation is [tex]\( x^2 = 3x - 1 \)[/tex].
To identify the quadratic term, we recognize the term with [tex]\( x \)[/tex] raised to the power of 2.
Here, it is clearly [tex]\( x^2 \)[/tex].
Thus, the quadratic term is [tex]\( \boxed{x^2} \)[/tex].
### Question 2: What is the numerical value of [tex]\( a \)[/tex] in the equation [tex]\( x(x - 4) = 14 \)[/tex] ?
First, expand the given equation:
[tex]\[ x(x - 4) = 14 \][/tex]
[tex]\[ x^2 - 4x = 14 \][/tex]
Next, reformat this into a standard quadratic equation form [tex]\( ax^2 + bx + c = 0 \)[/tex]:
[tex]\[ x^2 - 4x - 14 = 0 \][/tex]
In a quadratic equation of the form [tex]\( ax^2 + bx + c = 0 \)[/tex]:
- The coefficient of the [tex]\( x^2 \)[/tex] term is [tex]\( a \)[/tex].
Looking at the equation [tex]\( x^2 - 4x - 14 = 0 \)[/tex], we see that the coefficient of [tex]\( x^2 \)[/tex] is [tex]\( 1 \)[/tex].
Therefore, [tex]\( a = \boxed{-4} \)[/tex].
### Question 3: What is the constant term in the quadratic equation [tex]\( 7x^3 = -x^2 \)[/tex] ?
Rewriting the given equation:
[tex]\[ 7x^3 + x^2 = 0 \][/tex]
To identify the constant term, we normalize the equation into the form [tex]\( ax^2 + bx + c = 0 \)[/tex].
First, let's rearrange the equation from [tex]\( 7x^3 + x^2 = 0 \)[/tex]:
- There is no term with [tex]\( x \)[/tex] or a constant term without [tex]\( x \)[/tex].
So, the constant term is [tex]\( c = 0 \)[/tex].
Thus, the constant term in the equation is [tex]\( \boxed{0} \)[/tex].
### Summary of answers:
1. The quadratic term is [tex]\( \boxed{x^2} \)[/tex].
2. The numerical value of [tex]\( a \)[/tex] is [tex]\( \boxed{-4} \)[/tex].
3. The constant term is [tex]\( \boxed{0} \)[/tex].
We value your presence here. Keep sharing knowledge and helping others find the answers they need. This community is the perfect place to learn together. Thank you for trusting IDNLearn.com with your questions. Visit us again for clear, concise, and accurate answers.